Anxiety in Visually Impaired Students about the Future - Aydın Kızılaslan; M. Meral Kızılaslan (Institute of Advanced Engineering and Science, 2018)
The aim of this study is to determine the anxiety level that visually impaired students may have for the future when planning their profession. Anxiety is defined as excessive level fear and worry about real or imaginary situations. So the excessive worry can affect the ability to act to solve a problem. This study is a case study based on the semi-structured interviews. The study group consists of six 8th grade students with visual impairment. The aim of selecting students with visual impairment as a sample group is to determine the individuals who are aware that education is an important for their future plans but at the same time aware that the barriers created by society have greater impact on their the socialization. As a result, visually impaired individuals are willing to be part of the society, but the created obstacles cause anxiety in many different ways as they constitute their futures. This situation negatively affects their motivation and academic performance, and diminishes the importance of education for them as well.